Study on the Novel Photoluminescence Powder Synthesized from Zinc Carbonate Nanoparticles Associated with Fluorescein Dye for its Latent Fingerprint Detection - Kongsak Pattarith; Rachadaporn Benchawattananon (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
Fingerprint verification in crime scene is a basic method, but it is very important thing to be linked to the offender. Using fluorescent powder in passive fingerprint authentication will increase the performance of fingerprint detection for an identification. In this study, the new fingerprint powder has been synthesized by solvothermal method using zinc carbonate and fluorescein dye as main precursor using ethanol as a solvent. The synthetic fluorescent powder is also inspected for trial features with various diagnostic tools. As follows, detecting a micro texture with scanning electron microscope (SEM), absorption with UV-vis diffuse reflectance spectroscopy (DRS), examining the notation characteristics with X-ray diffraction (XRD) and UV light at wavelength 254 nm and 366 nm. Testing of the synthetic fingerprint fluorescent powder is done by swiping on the surface with a latent fingerprint. For studying optimum conditions affecting the fingerprint detection, there are general following types of textures including glass, metal, plastic and ceramics, and the appearance of smooth, curve and rough surfaces. It is also studies on the effects of duration and temperature of the retention affecting the fingerprints which have been inspected by the trial. For the synthetic fluorescent powder, its inspection can be used on each surface of different types with a good surface appearance. It has a long retention period of more than 30 days at room temperature and more than 15 days at a temperature of 90oC, and it can also be used to detect the fingerprints with a clear overlap. From this study, it is demonstrated that the synthetic fluorescent powder has a very excellent performance and has high possibility to be used to detect the passive fingerprints as an object witness in forensic processes.